Anatomy and powder microscopy of Curcuma sumatrana Miq. (Zingiberaceae) - RIVAL YUHENDRI; NURAINAS NURAINAS; TESRI MAIDELIZA; LINCE MERIKO; ALPONSIN ALPONSIN; IKARASTIKA RAHAYU ABDUL WAHAB (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Yuhendri R, Nurainas, Maideliza T, Meriko L, Alponsin, Abdul Wahab IR. 2024. Anatomy and powder microscopy of Curcuma sumatrana Miq. (Zingiberaceae). Biodiversitas 25: 900-908. Curcuma sumatrana is a wild plant endemic to West Sumatra and is believed to possess various therapeutic values that are beneficial in treating multiple diseases. This research aimed to characterize the anatomy of leaves, roots, and rhizomes through permanent preparations and powder microscopy to contribute to its phytochemical analyses. Observations of anatomical characteristics were carried out using a light microscope and photographed using the DP2-BSW application. The anatomical study of the leaf revealed its upper and lower epidermis thickness to be 49.8 ?m and 31.7 ?m, respectively. Furthermore, its mesophile thickness was 48.9 ?m, and the leaf type was unifacial, containing prism-shaped crystals, and covered with non-glandular trichomes. Its trichome height was 146.3 ?m, aerchyma area was 198.1 ?m, and vessel area was 284 ?m. On the other hand, the anatomical structure of the root showed cortex thickness of 292.7 ?m, endodermis thickness of 5.9 ?m, xylem diameter of 34.7 ?m and pith thickness of 244.6 ?m. Meanwhile, the anatomical structure of the rhizome consisted of eccentric starch, sand-shaped crystals, cortex thickness of 957 ?m, and endodermis thickness of 7.37 ?m. The powder analyses of its leaf showed clear structure of the xylem, epidermis, stomata, and trichomes. In contrast, its root and rhizome showed eccentric starch, spiral-type xylem vessels, fiber, oil glands, and cortex. In conclusion, the anatomical characteristics of C. sumatrana do not show significant differences from other species in the Curcuma genus, except in terms of the color of the rhizome. The rhizome of C. sumatrana is pale purple, while C. longa has a deep yellow rhizome, C. aeruginosa has a blue rhizome, and C. heyneana has a light yellow rhizome.